ANALISIS KEMAMPUAN KEUANGAN DAERAH PEMERINTAH KABUPATEN MAJENE - Sri Astuty Ratnasari Manggu (Yayasan Akrab Pekanbaru, 2019)
The purpose of this study was to analyze the financial capabilities of the Majene Regency government in 2014-2017, measured by the level of regional independence, the level of fiscal decentralization, the level of effectiveness of financial management and analysis of regional revenue and expenditure. The results of this study indicate that the financial capacity of Majene Regency in the 2014-2017 fiscal year was measured based on financial independence ratio, included in the criteria of regions with a very low level of independence. This is what causes the level of regional dependency to be very high, so that by itself the level of fiscal decentralization is also included in very less criteria. However, the effectiveness of revenues in Majene Regency has been quite effective, and must be continually improved so that it can reduce the financial dependence of Majene Regency on the central government. The financial capacity of Majene Regency in this case the level of regional independence and the level of fiscal decentralization will be even better if the Majene Regency government can increase the percentage of Regional Original Revenue revenues.